Differences in neural response to extinction recall in young adults with or without history of behavioral inhibition. (23rd May 2017) - Shechner, Tomer; Fox, Nathan A.; Mash, Jamie A.; Jarcho, Johanna M.; Chen, Gang; Leibenluft, Ellen; Pine, Daniel S.; Britton, Jennifer C.
Abstract: Behavioral inhibition (BI) is a temperament identified in early childhood that is associated with risk for anxiety disorders, yet only about half of behaviorally inhibited children manifest anxiety later in life. We compared brain function and behavior during extinction recall in a sample of nonanxious young adults characterized in childhood with BI ( n = 22) or with no BI ( n = 28). Three weeks after undergoing fear conditioning and extinction, participants completed a functional magnetic resonance imaging extinction recall task assessing memory and threat differentiation for conditioned stimuli. While self-report and psychophysiological measures of differential conditioning and extinction were similar across groups, BI-related differences in brain function emerged during extinction recall. Childhood BI was associated with greater activation in subgenual anterior cingulate cortex in response to cues signaling safety. This pattern of results may reflect neural correlates that promote resilience against anxiety in a temperamentally at-risk population.